Mathematics for physics students - Steiner, Robert V.; Schmidt, Philip A. (New York McGraw-Hill, 2011)
More than 1,500 fully solved problems. Hundreds more practice problems. Support for all major textbooks for physics.
Introduction to algebra -- Functions -- Graphs of functions -- Linear equations -- Simultaneous linear equations -- Quadratic functions and equations -- Inequalities -- The locus of an equation -- The straight line -- Families of straight lines -- The circle -- Rational and polynomial functions -- Trigonometric functions -- Exponential and logarithmic functions -- Complex numbers -- The calculus of single-variable functions : a mathematics approach -- The calculus of single-variable functions : a physics approach -- Vectors -- Polar, spherical, and cylindrical coordinate systems -- Multivariate calculus -- Elementary linear algebra -- Vector calculus : grad, div, and curl -- Vector calculus : flux and Gauss' Law -- Differential equations -- Elementary probability -- Infinite series.
Keywords: Mathematics -- Problems, exercises, etc; Physics -- Problems, exercises, etc